Mediating Role in Industry 4.0 (4IR) Adoptions and Sustainable Corporate Financial Growth in Developed Economies - Md Jawadur Rahim; Md. Jahidul Islam; Md. Nasirul Islam; Muhammad Ihsan Ibn Rahim (Journal of Governance and Accountability Studies, 2024)
Purpose: This study aims to explore the role of Industry 4.0 maturity in enhancing corporate financial performance in developed economies. It examines how technological innovation impacts Internal Business Process Performance (IBPP), Supply Chain Performance (SCP), and customer performance, which mediate financial outcomes. Methods: A survey was conducted among 110 manufacturing firms in the United States, selected from a database of 834 eligible companies. The study employed AMOS software for Structural Equation Modelling (SEM) to test hypotheses based on survey data. The maturity of Industry 4.0 technologies in these firms was measured using a comprehensive framework. Results: The study found that Industry 4.0 maturity significantly improves IBPP and SCP, positively affecting customer performance. Notably, customer performance serves as a full mediator between SCP, IBPP, and financial performance. Firms with higher Industry 4.0 maturity show better financial results due to improved customer engagement and satisfaction. Limitations: The study's findings are based on a sample of 110 firms, which limits generalizability. Future research with larger and more diverse samples is recommended. Contributions: This research contributes to understanding how Industry 4.0 technologies influence financial success, providing valuable insights for policymakers and business leaders in manufacturing sectors. Novelty: The study uniquely examines the complementary roles of IBPP, SCP, and customer performance in mediating the relationship between Industry 4.0 maturity and financial outcomes.